PERFORMANCE STUDY OF WOOD CHIPS GASIFICATION STOVE - fredy surahmanto (Universitas Sultan Ageng Tirtayasa, 2019)
This research aims at investigating the performance of a gasification stove with wood-chips as fuel and recognizing the factors affecting. The stove consisted of a reactor, a char chamber, and a burner. The fuel was fed into the reactor with a certain amount of primary air was flowed through the bottom part of the reactor, and then was ignited from the topside of the fuel. Meanwhile, combustion zone move down and left char that would be taken out after the process finished. Combustible gases resulted from reactions flowed to the burner where the secondary air enters through holes located at burner side combusted the combustible gases. The highest performance achieve was still relatively low (7.3 %), so that model design improvement is required. The stove performance could be possibly influenced by the following parameters, namely: combustion zone propagation rate, fuel consumption rate, and specific gasification rate, which all of them were very interrelated and indicated temperature stability that was proportional to the efficiency achieved. These were shown by stable water temperature profile obtained from boiling process during gasification. The more stable the process the higher the efficiency.